A type I AIE photosensitiser-loaded biomimetic nanosystem allowing precise depletion of cancer stem cells and prevention of cancer recurrence after radiotherapy. (April 2023) - Ning, Shipeng; Zhang, Tianfu; Lyu, Meng; Lam, Jacky Wing Yip; Zhu, Daoming; Huang, Qinqin; Tang, Ben Zhong
Abstract: Radioresistance of Cancer stem cell (CSC) is an important cause of tumor recurrence after radiotherapy (RT). Herein, we designed a type I aggregation-induced emission (AIE) photosensitiser-loaded biomimetic mesoporous organosilicon nanosystem (PMT) for precise depletion of CSC to prevent tumor recurrence after RT. This PMT system is composed of a type I AIE photosensitiser (TBP-2) loaded mesoporous organosilicon nanoparticles (MON) with an outer platelet membrane. The PMT system is able to specifically target CSC. Intracellular glutathione activity leads to MON degradation and the release of TBP-2. Type I photodynamic therapy is activated by exposure to white light, producing a large amount of hydroxyl radicals to promote CSC death. The results of in vivo experiments demonstrated specific removal of CSC following PMT treatment, with no tumor recurrence observed when combined with RT. However, tumor recurrence was observed in mice that received RT only. The expression of CSC markers was significantly reduced following PMT treatment. We demonstrate the development of a system for the precise removal of CSC with good biosafety and high potential for clinical translation. We believe the PMT nanosystem represents a novel idea in the prevention of tumor recurrence.